IMPROVING THE PRODUCTIVITY OF BUSINESS MICRO MICROBES IN WARNASARI VILLAGE - Trisa Nur Kania; Dindin Abdurohim; Latifah Adnani; Atin Hafidiah hafidiah (LPM Universitas Pasundan, 2020)
The problems faced by PKM Partners are on a number of factors that are difficult to be resolved by Partners, namely relating to production equipment that is worn, does not have a production permit, does not have a brand, has not been tested for product nutrition, has not been packaged with attractive performance. Therefore this activity aims to provide assistance so that the micro-businesses occupied by Partners can be further increased in the number and quality of products they produce. Service activities are carried out in the form of facilitation of production equipment, facilitation of product nutrition testing, financial management training and facilitation of product brand design. The results of the activity can be described that currently Partners: 1. already has the following new equipment Spinner to squeeze oil from freshly fried potato chips, 2. The oil content in the product has been reduced enough to be safe for consumption, 3. The nutritional content of the product is already known because it has been tested in the TP Lab the nutritional content contained in potato chips, 4. Already able to understand about the character of a superior entrepreneur and and will try to become a formidable business actor at the micro business level, 5. Partners are helped to design product brands, namely